Elective semaglutide prescription enabled waitlisting and transplantation of otherwise ineligible obese renal transplant candidates - Navaux, Emilie; La, Caroline; Dufour, Sylvain; Huberty, Vincent; Mourabit, Youssef; Caes, Thomas; Koliakos, Nikolaos; Mikhalski, Dimitri; Le Moine, Alain; Catalano, Concetta (Frontiers in Transplantation, 2025)
Although transplantation remains the treatment of choice for end-stage renal disease, patients suffering from severe obesity are too often unlisted for this reason. Pre-transplant bariatric surgery is not free of risk and the use of ‘Glucagon Like Peptide-1’analogues in these patients is limited. Our study aims to determine whether semaglutide administration enabled waitlisting and transplantation of otherwise ineligible obese renal transplant candidates. Between 01/01/2021 and 10/30/2023, patients rejected from renal transplantation because of obesity received pre-transplant subcutaneous semaglutide up to 1 mg/week. Of the 23 patients included, initial mean body weight, BMI and waist circumference were 102.9 Kg, 35.6 and 119.5 cm respectively. After a median of 12.2 months on semaglutide, these parameters decreased by 11.4 Kg (p ≤ 0.001), 3.9 points (p ≤ 0.001) and 9.6 cm (p ≤ 0.001) respectively. 56.5% of patients initially rejected for transplantation were listed within a median of 5.4 months, and 61.5% of them were transplanted. No major side effects were reported. In summary semaglutide administration enabled waitlisting and transplantation of otherwise ineligible obese renal transplant candidates. This treatment should be an integral part of the pre-transplant management of obesity.